Intra- and Interobserver Reliability of Superb Microvascular Imaging (SMI) Doppler for Assessing Placental Microvasculature - Rocio Garcia-Jimenez; José Antonio García-Mejido; Irene Valero; Ana Fernandez-Palacin; Carlota Borrero; Jose Antonio Sainz-Bueno (Clinical and Experimental Obstetrics & Gynecology, 2022)
Objective: Superb Microvascular Imaging (SMI) Doppler is a novel technique. We aim to evaluate intra- and interobserver reliability of SMI Doppler for the assessment of normal placental microvasculature. Materials and Methods: A prospective observational study was conducted including 11 pregnant patients. Ultrasonography placental assessment was performed on 28-weeks pregnant patients, by two expert examiners using SMI Doppler in one single visit. To evaluate interobserver reliability, the first examiner took measurements using SMI Doppler, followed then by the second examiner. Afterwards, the first examiner performed a second evaluation, in order to assess intraobserver reliability. Intraclass correlation coefficients (ICC) and Cohen’s Kappa coefficient, and their 95% confidence intervals, were estimated for quantitative and qualitative parameters, respectively. Results: Intraobserver reliability was found to be excellent for all quantitative parameters, with all ICC values above 0.97. For qualitative variables, excellent reliability was obtained for the number of secondary villi, while the number of tertiary villi had an adequate reliability with a Cohen’s Kappa coefficient of 0.792 (95% CI 0.38–1.17; p = 0.007). Interobserver ICCs ranged from 0.92 to 1.00 for all quantitative parameters, thus finding excellent interobserver reliability for all of them. An excellent reliability was also obtained for the number of secondary villi, while the reliability for the number of tertiary villi was found to be adequate. Conclusions: Our findings show that placental microvasculature measurements obtained by a single or two different examiners are reliable and reproducible. The good intra- and interobserver reliability results of SMI Doppler showed in our study stress the value of this technique in the evaluation of placental microvasculature, and thus research in this field is the step forward for the assessment of placental insufficiency.